1992
DOI: 10.1103/physrevc.45.r509
|View full text |Cite
|
Sign up to set email alerts
|

Pion absorption in heavy nuclei

Abstract: Cross sections have been measured for proton emission following r+ absorption on Li, C, Al, Ni, Sn, Pb, and Q for pion kinetic energies of 50, 100, 150, and 200 MeV by using a large-solid-angle bismuth germanate detector array. An increasing fraction of transitions to states of large missing energy and with particles other than protons is observed as the energy and mass increase. PACS numbers: 25.80.Ls Despite much study [1], pion absorption is still not well understood in detail, even in light nuclei. Most st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The first is that the angular distributions for the pp, pd and dd final states are nearly identical in shape, with the pd distribution slightly flatter than the pp distribution, and the dd distribution the flattest of all. This similarity was reported earlier for pd emission from a variety of nuclei by Ransome et al [8] who concluded "that most deuteron emission is probably due to neutron pick-up by protons". Unfortunately, however, the poor angular resolution of the BGO Ball data did not allow this hypothesis to be tested in a more quantitative manner.…”
Section: Monte Carlo Modelssupporting
confidence: 70%
“…The first is that the angular distributions for the pp, pd and dd final states are nearly identical in shape, with the pd distribution slightly flatter than the pp distribution, and the dd distribution the flattest of all. This similarity was reported earlier for pd emission from a variety of nuclei by Ransome et al [8] who concluded "that most deuteron emission is probably due to neutron pick-up by protons". Unfortunately, however, the poor angular resolution of the BGO Ball data did not allow this hypothesis to be tested in a more quantitative manner.…”
Section: Monte Carlo Modelssupporting
confidence: 70%
“…This is evaluated from differences between external pion interaction data [40][41][42][43][44][45][46][47][48][49][50][51] and the underlying GEANT4 simulation. The external data do not cover the whole momentum range of T2K, so some extrapolation is necessary.…”
Section: Nd280 Detector Systematicsmentioning
confidence: 99%
“…ese interactions are known as nal state interactions p → π + n, and absorption on nucleons is simulated. e cross sections for these interactions are tied to several external pion-nucleus scattering measurements [161,[189][190][191].…”
Section: Coherent and Diffractive Pion Productionmentioning
confidence: 99%